The Importance of Supervision for Optimizing the Performance of Madrasah Principals and the Quality of Educational Institutions - Farida Isroani, Fahru Rozi, Zaini Miftah, Mas Tajudin Ahmad, Zaenullah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Educational supervision is a process carried out by superiors, such as school principals or supervisors, to their subordinates, namely teachers and other education personnel, with the aim of improving the performance and quality of education. Supervision in education does not only focus on administrative supervision; it also includes guidance and mentoring aimed at helping teachers improve their professional abilities, increase teaching effectiveness and optimize student learning outcomes. With good supervision, teachers can get useful feedback about their performance, receive guidance in curriculum development and implementation and receive positive feedback about how they are succeeding. Good supervision also helps create a collaborative and supportive work culture among teachers, which ultimately increases their motivation and commitment to the teaching profession